The Obsolescence of Man in The Digital Society - Maillard, Dominique (Bright Institute, 2021)
Commenting on the limitations of Man after the moral disasters of World War II and the logics of production inherent to the second industrial revolution, GuntherAnders had concluded to the “obsolescence of Man”. Anders pointed to the